Protocol for olfactory training in persisting COVID-19-associated loss of smell (SMELL): a monocentric randomised controlled trial conducted in Innsbruck - Raimund Helbok; Atbin Djamshidian; Günter Weiss; Klaus Seppi; Beatrice Heim; Georg Goebel; Nicolas De Cleene; Frank Jagusch; Joachim Schmutzhard; Timo Gottfried; Marina Peball; Philipp Ellmerer; et al. (BMJ Open)
Introduction Olfactory dysfunction (OD) following COVID-19 affected up to 70% of patients, with more than 30% still reporting lingering symptoms a year later. Treatment is essential, as previous research has linked (postviral) OD to depression, impaired quality of life (QoL) and even heightened mortality rates.Methods and analysis We designed a monocentric, single-blinded randomised controlled trial evaluating the efficacy of olfactory training (OT) in individuals with persisting COVID-19-associated loss of smell. Randomisation will be done in a 1:1 manner. OT will be performed using the Sniffin’ Sticks Duft Quartett over a period of 12 weeks, two times per day. The primary endpoint of this study is the change in olfactory score between baseline and after 12 weeks, measured by the combined score of the identification and discrimination subscales of the Sniffin’ Sticks testing battery. QoL, overall health, mood, personal well-being and symptom severity will be assessed at baseline and during a follow-up visit, using multiple validated questionnaires and scales. OT is offered to the second cohort during an open-label phase extension. This manuscript highlights and discusses the study protocol.Ethics and dissemination Ethical approval for the study was obtained from the Ethics Commission of the Medical University of Innsbruck, Austria. Results of this study will be shared through conferences and publications in peer-reviewed journals.Trial registration number NCT05421221.